INTERNAL LOCUS OF CONTROL MEMODERASI COMPUTER ANXIETY DAN COMPUTER ATTITUDE PADA KEAHLIAN APLIKASI KOMPUTER AKUNTANSI - Krisna Dewi, Ni Komang Urip; Juliarsa, Gede (E-Jurnal Akuntansi; Vol 19 No 1 (2017), 2017)
The purpose of this study is to determine the effect of computer anxiety , computer attitude , internal locus of control, and the effect internal locus of control as moderating variabel to moderate computer anxiety and computer attitude to self efficacy in using accounting software/ CSE. This study use survey metode with questinnaire technique for data collection and analysis techniques of multiple linear regression and Moderated Regression Analysis (MRA) which includes classical assumption and hypothesis testing using partial test and coefficient of determination. Based on the analysed data the results obtain are as follows, computer anxiety effect negatively, computer attitude effect positively, internal locus of control effect positively, internal locus of control have weaken to negative effect of computer anxiety to self efficacy in using accounting software and internal locus of control have strengthen to positive effect of computer attitude to self efficacy in using accounting software.
Keywords: computer anxiety, computer attitude, internal locus of control, Computer Self Efficacy (CSE)